(untitled) (Comprehensive Journal of Science, 2026)
The global expansion of mobile communication technologies has increased exposure to radiofrequency electromagnetic fields (RF‑EMF). Although RF radiation is categorized as non‑ionizing, growing experimental evidence suggests that prolonged exposure may influence biological systems through oxidative stress mechanisms (Dasdag & Akdag, 2016; Yakymenko et al., 2016). This study presents a literature‑based experimental model evaluating potential hematological and oxidative responses to chronic RF‑EMF exposure. Modeled data were derived from previously published experimental investigations examining mobile phone radiation in the 900–1800 MHz frequency range (Wang & Zhang, 2017; Kıvrak et al., 2017). Simulated exposure conditions included 6 hours of daily radiation for 60 consecutive days. Modeled results indicate reductions in erythrocyte indices and increased leukocyte counts, accompanied by elevated lipid peroxidation marker malondialdehyde (MDA) and decreased antioxidant enzymes superoxide dismutase (SOD), glutathione (GSH), and catalase (CAT). These patterns are consistent with mechanisms previously reported in experimental RF‑EMF studies (Zothansiama et al., 2017; Henschenmacher et al., 2022) and support oxidative imbalance as a central pathway underlying biological interaction with radiofrequency radiation.